Rekayasa Aplikasi Edutainment Untuk Mengembangkan Sensor Motorik Pada Anak–Anak Berbasis Desktop - Seprian, Adam; Astuti, Lastri Widya; Ramadhan, Mustafa (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2024)
Edutainment comes from education, which means education, and entertainment, which means entertainment. So, in terms of language, education is entertaining. In this case, fun learning is usually done with humor, games, role-playing, and demonstrations. Learning can also be done in other ways as long as it can provide fun learning for students. At this age, they are in the most rapid growth and development period, both physically and mentally. Therefore, the author created a desktop-based edutainment application to develop motoric sensors in children that can accelerate growth with the hope that children can directly use the game application and gain more knowledge and change learning patterns not to be bored. This edutainment application is a learning application for early childhood ages ranging from 3 to 6 years, and it contains material for learning letters, numbers, pictures, and counting. The research method and development of this edutainment application is the rational unified process (RUP) method, a software engineering method developed by collecting various best practices in software.